Pests and pets - Warner, Andy (Andy Warner's oddball histories., 2021)
Illustrated guide to various domesticated animals and those that have adapted to human behavior, describing their history, use, and relationship with humans. Includes an illustrated timeline of domestication and a map of animal origins.